Greetings of Thai speakers: Content and linguistic strategies - Kasa, Deeana (Kasetsart Journal of Social Sciences, 2021)
Greetings are universal routines. However, greetings in different cultures have different conditions. Greetings among Thai speakers may lead to misunderstanding to non-native Thai speakers even at the beginning of the conversation. This research, therefore, aims to study content and linguistic strategies in greetings of Thai speakers based on Ethnomethodology through participant observation. It was found that the content focuses on the speaker, the hearer and the referent, and there are two types of linguistic strategies, namely, direct greetings and indirect greetings. Greetings in Thai society seem to reflect how speakers pay attention to hearers. Communication participants in the society are bound together and interact with a few utterances in greetings.